Resurgence of hypertension and cardiovascular diseases in patients recovered from COVID-19: An Indian perspective - Krishnakumar, Bhaskaran; Christopher, Johann; Prasobh, P; Godbole, Shreerang; Mehrotra, Anurag; Singhal, Anurag; Roy, Satrajit; Bhattacharya, Kuntal; Kolte, Narendra; Abhyankar, Mahesh; Revankar, Santosh (Journal of family medicine and primary care, 2022)
Objective: The aim of this study was to understand the prevalence, extent, clinical approach of hypertension and cardiovascular disease (CVD) in patients recovered from COVID-19. Methods: The round table meetings (RTMs) and survey convened a diverse panel of specialists including cardiologists, endocrinologists, diabetologists, consultant physicians, and family physicians from various geographical zones of India. A standard questionnaire including 10 questions was developed pertaining to the resurgence of hypertension and CVD in patients recovered from COVID-19. The RTMs and survey were held virtually. The collected opinions and recommendations were compiled to derive a consensus document. Results: A stotal of 3066 health-care practitioners (HCPs) participated. Hypertension was the most prevalent comorbidity in patients recovered from COVID-19 followed by diabetes, dyslipidemia, and coronary artery disease. Almost two-thirds of HCPs reported that 10%-30% newly diagnosed hypertension in patients recovered from COVID-19. Uncontrolled hypertension in 10-20% of COVID-19 recovered patients opined by 45% of the HCPs. About, 35% HCPs reported CV complications in 10-20% of Covid-19 recovered patients and 63% HCPs reported exacerbations of CAD in 10-30% of patients. Majority of HCPs preferred to switch to dual combination therapy from monotherapy for hypertension management (52.0%) and ARBs and its combination is most preferred combination for hypertension control (60%). Majority of the HCPs suggested follow-up after 1-2 weeks (39.0%). Close monitoring on symptoms including chest pain and breathlessness (45.0%), adherence to medication and regular monitoring of lab parameters (25%) is recommended for these patients. Conclusion: Overall observations indicate an increased incidence of hypertension and CVDs post recovery from COVID-19. A dual therapy of ARBs was the preferred choice for management of hypertension. Regular follow-up and close monitoring of symptoms to prevent further CV complications in COVID-19 recovered patients is recommended.